Role of microbiota in the pathogenesis of functional disorders of the lower GI tract: Work in progress. Issue 10 (October 2017) - Jalanka, Jonna; Spiller, Robin
Abstract: Functional bowel disorders affect a significant proportion of people word wide. Patients suffer from longstanding symptoms of abdominal pain or discomfort in combination with abnormal bowel habits. The evidence for role of microbiota is currently contradictory and descriptive. This review aims to summarize the reasons which include methodological differences in DNA extraction and sample handling along with other factors such as diet, prior antibiotic use and transit, all important major determinants of microbiota which are difficult to control. Randomized studies of specific intervention in which such factors are varied may improve reproducibility and consistency of findings in future research.